Digital marketing fundamentals : from strategy to ROI - Visser, Marjolein; Sikkenga, Berend; Berry, Mike, 1958- (Noordhoff : Routledge, 2021)
Marketing is now fundamentally a digital process, and this textbook was the first to comprehensively analyse marketing through a digital lens. As the field is evolving rapidly, this edition is fully updated to cover the latest developments in theory and practice, incorporating many international examples and cases.
Keywords: internetový marketing; sociální média; investice; marketing; Internet marketing; social media; investments; učebnice; textbooks